International perspectives of diversity, equity, and inclusion - King, Eden; Roberson, Quinetta; Hebl, Mikki (Emerald Publishing Limited, 2025)
International Perspectives of Diversity, Equity, and Inclusion, the seventh in the Research in Social Issues in Management series, includes a collection of contributions from around the globe. The amalgamation of these perspectives together broadens the scope of diversity, equity, and inclusion (DEI) research and practice and offers insights that extend beyond the U.S.-focused research that dominates the field. This book addresses unique facets of organizational diversity and brings to bear diverse cultural contexts, historical legacies, and socio-political considerations from regions as varied as South Korea, England, Ireland, Puerto Rico, Norway, Australia, Germany, Malaysia, Japan, Canada, France, India, Belgium, and Sweden. The contributions challenge prevailing assumptions and expand the theoretical and practical boundaries of the field by providing actionable strategies through which to approach DEI in more culturally sensitive and globally relevant ways.
Keywords: Equality.; Social integration.; Diversity in the workplace.; Cultural pluralism.; Social Science -- Diversity & Multiculturalism.; Social Integration and assimilation.; Cross-cultural, Intercultural studies and topics.; Ethnic groups and multicultural studies.; elektronické knihy; electronic books